Engineering thermal hysteresis of ferromagnetic shape memory alloy sensory particles. (May 2022) - Cho, W.; Salas, D.; Barta, N.; Karaman, I.
Abstract: Simultaneous magnetic and martensitic phase transitions in NiMn-based particles embedded in a metallic matrix could be stress-induced by crack propagation, making them candidates as sensory particles in structural health monitoring. For such applications, the particles should be small to maintain matrix properties, but large enough to martensitically transform at desired temperatures, requiring their transformation characteristics to be tailored. Here, the effects of heat treatments on the transformation characteristics of micron-sized Ni45 Co5 Mn36.7 In13.3 particles are studied to demonstrate such tailorability. It is discovered that martensitic transformation temperatures are proportional to the annealing temperature below the order-disorder (ODO) transition and inversely proportional above it, and an opposite trend is observed for the transformation hysteresis. These findings are in agreement with the bulk behavior, however, a significantly larger hysteresis was found in the particles, which was correlated with crystallite size dependent phenomena, increasing the effective energy barrier to the phase-transition. Graphical abstract: Image, graphical abstract